Kejujuran sebagai Kearifan Lokal di SMKN 1 Wonosari - Thoriq Nurmadiansyah (ESENSIA: Jurnal Ilmu-Ilmu Ushuluddin, 2012)
This article discusses the development of local wisdom SMKN 1 Wonosari.  Local Wisdom are closely related to honesty was initiated in order to strengthen the nation's character. The study was conducted in the cafeteria honesty SMKN 1 Wonosari. "Canteen" honesty is honesty canteen canteen that still exists among the other folded. Existence to be an example for other schools, in addition to the creation of a culture of honesty also cleanliness can not be denied, and more importantly the quality of the food is guaranteed. Unequaled achievement is "Cafeteria Honesty" is able to create a culture of self-awareness and honesty without having watched someone else.